Long‐Lasting Effects of Chronic Intermittent Alcohol Exposure in Adolescent Mice on Object Recognition and Hippocampal Neuronal Activity. (1st November 2016) - Beaudet, Gregory; Valable, Samuel; Bourgine, Joanna; Lelong‐Boulouard, Véronique; Lanfumey, Laurence; Freret, Thomas; Boulouard, Michel; Paizanis, Eleni
Abstract : Background: Binge drinking is popular and highly prevalent in teenagers. However, the long‐term cognitive and neurobiological consequences of such practices are not yet fully understood. In this context, we therefore assessed in mice whether a chronic intermittent alcohol (CIA) exposure in adolescence had long‐term consequences on object discrimination and memory performances, emotional behaviors, brain activity, and morphology. Methods: C57BL/6JRj mice were treated with either saline or ethanol (EtOH) (2 g/kg/d, i.p., from postnatal days [PND] 30 to PND 44 every other day). The day following the last administration or later in adulthood (PND 71) mice were tested for different behavioral tests (novel object recognition, spontaneous alternation, light–dark box, elevated plus‐maze, actimeter test), to assess object recognition, working memory performances, anxiety‐like behavior, and locomotor activity. We also investigated neuronal activation of hippocampus, prefrontal and perirhinal cortices, and anatomical changes using immediate‐early gene expression and longitudinal brain magnetic resonance imaging. Results: Our results showed that adolescent mice exposed to CIA present a critical and persistent impairment of short‐term object recognition performances. By contrast, spatial working memory was not impaired, nor was anxiety‐like behavior. This altered object discrimination was associated with a biphasic change in neuronal activity in the hippocampus but without morphological changes. Indeed, c‐Fos expression was specifically increased in the dorsal dentate gyrus (DG) of the hippocampus after the binge exposure, but then became significantly lower in adulthood both in the DG and the CA1 part of the hippocampus compared with adult saline pretreated mice. Conclusions: These findings provide evidence for adolescent vulnerability to the effects of intermittent binge EtOH exposure on object discrimination and hippocampal activity with long‐lasting consequences. Abstract : The long‐term cognitive and neurobiological consequences of binge drinking in adolescence are not yet fully understood. This study demonstrates that chronic intermittent alcohol exposure specifically and sustainably affects object recognition performances in adolescent mice. This specific adverse effect may rely on a differential recruitment and vulnerability of brain structures for novelty detection compared to adult mice. Adolescent mice were compared with adult exposed to the same paradigm or to adult pretreated in adolescence (# p <0.05, ## p <0.01, ### p <0.001: significant difference from chance exploration).